2019
DOI: 10.5194/aab-62-241-2019
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between insulin-like growth factor-1 (IGF-1) concentrations and body trait measurements and climatic factors in prepubertal goat kids

Abstract: This study aimed to investigate relations between insulin-like growth factor-1 (IGF-1) concentrations and some body trait measurements (body weight, withers height, rump height, body length, chest depth, chest width, chest girth and cannon bone circumference) and climatic factors in prepubertal male and female White (75 % Saanen and 25 % Kilis goat) and Angora goat kids. For this purpose, blood samples were regularly taken from the vena jugularis, and body trait measurements were regularly carried out (every 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
2
9
0
3
Order By: Relevance
“…These authors observed that treatment with artificial long days to goat kids from d 4 up to 27 d of age induces a greater daily weight gain in males than in females. Similarly, Pehlivan (2019) found that, only in males and not in female kids, IGF-I concentrations (which are related to their growth) are positively correlated with BW, withers height, rump height, body length, and chest depth. In our study, the positive correlation between mean milk yields of dams with the daily weight gain in male kids ( Figure 6) supports previous observation that the BW gain of kids is directly related to the level of their dam's milk yield (García y González et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…These authors observed that treatment with artificial long days to goat kids from d 4 up to 27 d of age induces a greater daily weight gain in males than in females. Similarly, Pehlivan (2019) found that, only in males and not in female kids, IGF-I concentrations (which are related to their growth) are positively correlated with BW, withers height, rump height, body length, and chest depth. In our study, the positive correlation between mean milk yields of dams with the daily weight gain in male kids ( Figure 6) supports previous observation that the BW gain of kids is directly related to the level of their dam's milk yield (García y González et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…De manera general, el modelo estadístico reveló un efecto del transcurso de la edad de los animales sobre esas variables (P < 0.05), excepto el largo del cuello cuyo incremento no fue significativo. Estos resultados son similares a los reportados en cabritos machos White (cruzas entre Saanen y cabras Kilis) y en los de la raza Angora en los que se observó un incremento importante en la altura a la cruz y en el largo del cuerpo de la semana 13 a la semana 20 de vida (Pehlivan, 2019). En el presente estudio, en la mayoría de estas mediciones corporales no existió diferencia significativa entre los 2 grupos (P > 0.05).…”
Section: Resultados Y Discusiónunclassified
“…También en vacas lactantes, la exposición a días largos incrementó la expresión de genes a leptina y el número de sus receptores en el tejido adiposo (Bernabucci et al, 2006). Otra posible explicación del efecto estimulatorio de los días largos sobre el peso corporal y la GDP de los machos cabríos del presente estudio es que es bien sabido en caprinos y en ovinos que la exposición a días largos artificiales incrementa las concentraciones de la hormona del crecimiento (GH) y del factor de crecimiento similar a insulina (IGF-1; Schanbacer y Crouse, 1980; Jin et al, 2013;Flores et al, 2018;Pehlivan, 2019). Por lo que es probable que en los machos del GDL del presente estudio haya existido un mayor estimulo del crecimiento mediado por dichos factores hormonales.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Our results in goats showed a reduction by 93% at 4 days postpartum, which was kept at the same levels at 7 days postpartum, showing that the trend of reduction in IGF-1 in goat colostrum was similar to cattle. A positive correlation between kid's blood IGF-1 concentrations and some body trait measures was found in goats during the prepubertal period (up to 5 months old) [42]. However, another hormone such as thyroid hormone later had a positive effect on growth and mohair production of kids [43].…”
Section: Transition From Colostrum To Milkmentioning
confidence: 97%